Experiential Learning: Early Childhood Education Learning Innovation that Fosters Children's Activeness and Curiosity - Agus Tantriningsih, Hestin; Istiatik, Dasih Irma; Maemunah, Sari; Surtinah, Wiwin; Riadi, Refren; Imron, Moch Ali; Susanti, Anna Astrid (Santoso Academy Network, 2025)
This community service program aims to improve the digital business skills of PKK mothers in Kampung Sengon, Depok, by introducing the use of social media as a practical marketing tool. The training, held on January 4, 2024, focused on familiar platforms such as WhatsApp, Instagram, and Facebook and covered basic digital marketing techniques, affiliate marketing, and e-commerce strategies suitable for micro, small, medium-entrepreneurs (MSME). Delivered through lectures and interactive discussions, the program significantly improved participants' understanding of digital entrepreneurship, increased their motivation, and opened up opportunities for collaboration. The training emphasized the importance of building a consistent digital presence to develop their businesses independently and sustainably. Managerial implications highlight the need for an adaptive and participant-centered approach in training design, ensuring that content is aligned with participants' digital skills. Facilitators should also provide access to digital tools and encourage peer-to-peer interactions to strengthen learning outcomes and support the formation of informal business networks. Ultimately, the program contributes to improving household economic resilience and driving local economic development.